Comparison of Body composition among different Level of Students - Bhavani, A. (International Journal of Fitness, Health, Physical Education & Iron Games Volume: 2, No: 1, Jan 2015- June 2015, 2015)
Body composition is defined as the proportion of fat, muscle, and bone in the body. It is usually given as a ratio of lean mass to fatty mass. Body composition will normally be expressed as either a percentage of fat or as a percentage of lean body mass.The study was designed to compare the body composition of different level of students (School, College, and University). To achieve the purpose of the study 1500 subjects were selected in this study (School-500, College-500, and University-500). The age of the subjects ranged for school students between 14-17 years, College 18-21 years, and University 22-25 years. In this study one of health related physical fitness variablenamely body composition (Percent Body Fat) is selected as criterion variable. Selected variable is tested by following standardized test of sum of skin fold site. One way analysis of variance was applied to find out whether there was any significant difference on body composition among different level of Students. The level of significance was fixed at 0.05, if the obtained F ratio is significant, Scheffe’s post hoc test was applied to find out the means difference. The results of the study show that there was a significant difference among the students on body composition. Further it reveals that, between the different levels of students body composition shows significant difference. It is concluded that school boys were having significantly more per cent body fat than the College and University Students. Prior to adolescence per cent body fat was increases because of to meet out the bio-logical needs.
Keywords: Health related physical fitness; Body Composition; Percent Body Fat; Skin Fold thickness